2009
DOI: 10.1002/vnl.20181
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 1,5‐pentanediol dibenzoate as a potential “green” plasticizer for poly(vinyl chloride)

Abstract: 1,5-Pentanediol dibenzoate (PDDB) was evaluated as a potential ''green'' plasticizer for poly(vinyl chloride) (PVC) at concentrations ranging between 20 and 80 parts by weight per hundred parts of resin. The results of glass transition temperature (T g ) and tensile tests of PDDB blends with PVC were compared with those for blends of the commercial plasticizers di(2-ethylhexyl) phthalate (DEHP), di(ethylene glycol) dibenzoate (DEGDB), and di(propylene glycol) dibenzoate (DPGDB) in PVC. The depression in T g a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 27 publications
2
39
0
5
Order By: Relevance
“…These alternative plasticizers were selected for leaching tests based on their ability to lower the glass-transition temperature of PVC, as well as for their plasticization, biodegradation and mechanical testing results which have been shown to be comparable to that of DEHP (Erythropel et. al, 2012;Firlotte et al, 2009). …”
Section: Plasticizersmentioning
confidence: 97%
See 1 more Smart Citation
“…These alternative plasticizers were selected for leaching tests based on their ability to lower the glass-transition temperature of PVC, as well as for their plasticization, biodegradation and mechanical testing results which have been shown to be comparable to that of DEHP (Erythropel et. al, 2012;Firlotte et al, 2009). …”
Section: Plasticizersmentioning
confidence: 97%
“…Many alternatives have been proposed but not all combine the desirable properties required of the plasticizer during use and after disposal. Our group has investigated the synthesis and design of alternative PVC plasticizers (Erythropel et al, 2012), the biodegradation of alternative plasticizers , as well as the polymer processing and mechanical properties of alternative plasticizers in PVC (Firlotte et al, 2009). The ideal alternative to DEHP must satisfy many criteria but one crucial criterion is to minimize the plasticizer leaching rate from PVC mixtures into the environment.…”
Section: Introductionmentioning
confidence: 99%
“…To tackle the problems arising from the widespread use of DEHP, recent research aims at producing equally effective plasticizers that are more biodegradable and less toxic than DEHP and would thus be eliminated more quickly in the environment, an idea that can also be extended to the metabolites of this plasticizer (Erythropel et al 2013;Erythropel et al 2012;Firlotte et al 2009;Pour et al 2009a;Pour et al 2009b;Shi et al 2011;Stuart et al 2010). There also exist many commercial efforts to create plasticizers that are less toxic and recalcitrant; however, formulations of these compounds are often unknown.…”
Section: Perspectivesmentioning
confidence: 99%
“…Di(ethylene glycol)dibenzoate and di(propylene glycol)dibenzoate were shown to form toxic, stable metabolites when treated with yeast [55]. The related chemical 1,5-pentanediol dibenzoate shows improved biodegradability [56]. The outlook is promising, but it was reported that a technical-grade plasticizer containing predominantly di(propylene glycol) dibenzoate showed estrogenic properties [47], so more thorough testing is needed.…”
Section: E S Beach Et Almentioning
confidence: 99%